Conocimientos y actitudes sobre tratamiento de tuberculosis en usuarios atendidos en el establecimiento de salud Morona Cocha Iquitos 2019 - Ruiz Davila, Jairo (2024)
The general objective was to determine the relationship that exists in the knowledge and attitudes about tuberculosis treatment in users treated at the Morona Cocha health facility. The quantitative method was used through the correlational descriptive design. The population consisted of 78 people with tuberculosis, treated at the Morona Cocha health facility. Technique: the survey, Instruments: A Questionnaire based on knowledge about pharmacological treatment, home care and prevention of tuberculosis and a Likert-type scale on the attitude towards tuberculosis treatment. For the association analysis, Kendall's Tau-b test and the SPSS data package were used. The results obtained were: of the 52 (66.7%) patients with a more positive attitude towards tuberculosis treatment, 28.2% (22 patients) presented a regular level of knowledge and 38.5% (30 patients) a poor knowledge. Regarding the 26 (33.3%) patients with a less positive attitude towards tuberculosis treatment, 2.6% (2 patients) had good and fair knowledge, respectively, and 28.1% (22 patients) poor knowledge. The work concluded that there is a significant relationship between the level of knowledge about tuberculosis and the attitude towards treatment in patients with tuberculosis.